E-LEARNING AS A PLATFORM IN STUDYING ENGLISH AMONG EFL LEARNERS: BENEFITS AND BARRIERS - Erwin Oktoma; Muhammad Aprianto Budie Nugroho; Yayan Suryana (English Review: Journal of English Education, 2023)
This paper presents research findings on the benefits and barriers of E-learning in the study of English among EFL learners. The topic of this research was students from Department of English Education, Universitas Kuningan, and it was carried out using a qualitative design. An observation checklist and an interview were used to collect data. The study's findings revealed that using E-learning to study English has several benefits, including the flexibility of time and place, easy access to a wealth of information, the ability to facilitate relationships between learners through the use of discussion forums, and the ability to learn at one's own pace. And E-learning also has a numerous barriers in studying English such as, the lack of internet access/WIFI, a software barrier, learners are not enough excited to study English using E-learning, socially disconnected, weak levels of student engagement and students are illiterate and uneducated in the use of modern technologies. Therefore, it could be concluded that the use of E-learning in studying English at Department of English Education, Universitas Kuningan is not effective.